Inversion of the Temperature and Depth of Geothermal Reservoirs Using Controlled Source Audio Frequency Magnetotellurics and Hydrogeochemical Method - Zhao, Gui; Liu, Yanguang; Hu, Longhua; Bian, Kai; Qin, Shenjun; Liu, Feng; Hu, Jing (Frontiers in Earth Science, 2022)
Using the simple combination of traditional geophysical and geochemical methods in the detection of the depth and temperature of deep geothermal reservoirs results in great uncertainty. Given this, taking the Qutan geothermal field as an example, this study investigated the use of alternative methods, namely the multi-information joint detection using the controlled source audio-frequency magnetotellurics (CSAMT) method and geothermometers. First, the geochemical method was used to estimate the reservoir temperature and the depth of geothermal water circulation. Then, the relationship between the CSAMT resistivity and temperature of strata was explored using borehole temperature measurement. Based on this, the depth and temperature of geothermal reservoirs were estimated. The results show that the shallow reservoirs in the Qutan geothermal field have a top burial depth of approximately 423 m, a thickness of about 300 m, a temperature of about 79°C, and a fluid circulation depth of about 1959 m.